Humoral and cellular responses to a fifth bivalent SARS-CoV-2 vaccine dose in patients with immune-mediated inflammatory diseases on tumour necrosis factor inhibitors: a prospective cohort studyResearch in context - Hilde S. Ørbo; Taissa de Matos Kasahara; Asia-Sophia Wolf; Kristin H. Bjørlykke; Joseph Sexton; Ingrid Jyssum; Anne T. Tveter; Guri Solum; Ingrid Fadum Kjønstad; Sabin Bhandari; Ingrid E. Christensen; Tore K. Kvien; et al. (Elsevier, 2025)
Summary: Background: As most people now have established hybrid immunity, the need for regular, updated SARS-CoV-2 vaccine boosters in patients with immune-mediated inflammatory diseases (IMIDs) is unclear. The study aim was to assess humoral and cellular immunogenicity of a fifth bivalent vaccine dose in patients with IMID on tumour necrosis factor inhibitors (TNFi). Methods: In the longitudinal, observational Nor-vaC study, we assessed anti-spike and neutralising antibodies against Wuhan, Omicron BA.1 and BA.4, as well as frequency and polyfunctionality of responding T cells, following a fourth monovalent and a fifth bivalent (BA.1 or BA.4/5) vaccine dose in patients with or without hybrid immunity using TNFi. Findings: Between December 17, 2021, and June 20, 2023, 456 infection-naïve patients with IMIDs using TNFi received a fourth vaccine dose and were otherwise eligible for inclusion. A total of 373/456 (82%) received a fifth vaccine dose, of these 190/373 (51%) had hybrid immunity defined as having had COVID-19 between the fourth and fifth dose. In patients with hybrid immunity, the fifth dose did not induce improved humoral responses compared to infection, neither with BA.1 (median anti-spike antibody concentrations 23,244 IU/ml (IQR 15,138-45,233) vs 36,341 IU/ml (11,887-53,710), p = 0.52) nor BA.4/5 (31,693 IU/ml (15,176-54,186), p = 0.30). Comparison of neutralising antibodies yielded similar results. In infection-naïve patients, a fifth BA.4/5 vaccine, but not the BA.1, induced slightly higher humoral responses (18,890 IU/ml (6494-50,211)) compared to the fourth dose (7304 IU/ml (3245-17,260), p < 0.0001). CD8 T cell responses remained stable following a fourth dose (median frequency of spike-specific cells 0.039% (IQR 0.010-0.14)), infection (0.058% (0.026-0.17)) and a fifth dose (0.058% (0.013-0.20). Interpretation: In patients on TNFi with hybrid immunity, there was no immunological benefit of an updated fifth SARS-CoV-2 booster dose. Stable CD8 cellular responses following four doses indicate established protective immunity. Patients whose only risk factor is TNFi may in future follow vaccine recommendations for the general population. Funding: The South-Eastern Norway Regional Health Authority, The Coalition for Epidemic Preparedness Innovations (CEPI), Diakonhjemmet Hospital, Akershus University Hospital, Oslo University Hospital, University of Oslo, The Norwegian Research Council.